The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1038/sj.hdy.6800909
|View full text |Cite
|
Sign up to set email alerts
|

Biometrical genetic analysis of luteovirus transmission in the aphid Schizaphis graminum

Abstract: The aphid Schizaphis graminum is an important vector of the viruses that cause barley yellow dwarf disease. We studied the genetic architecture of virus transmission by crossing a vector and a non-vector genotype of S. graminum. F1 and F2 hybrids were generated, and a modified line-cross biometrical analysis was performed on transmission phenotype of two of the viruses that cause barley yellow dwarf: Cereal yellow dwarf virus (CYDV)-RPV and Barley yellow dwarf virus (BYDV)-SGV. Our aims were to (1) determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 66 publications
5
25
0
Order By: Relevance
“…The DIGE expression data were first compared between the three transmission-competent genotypes (Sg-F, A3, and CC6) and the refractive parent genotype Sg-SC. These spots were selected without regard to their expression in the refractive F2 genotypes, since the genes controlling virus transmission are additive in effect (8,9,34), and as we expected, the refractive F2 genotypes expressed some of the proteins in a manner similar to that of the competent genotypes. Thirty-two such spots were identified (Tables 2 and 3), 13 of which were aphid proteins upregulated in the competent genotypes and 7 of which were downregulated in the competent genotypes ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The DIGE expression data were first compared between the three transmission-competent genotypes (Sg-F, A3, and CC6) and the refractive parent genotype Sg-SC. These spots were selected without regard to their expression in the refractive F2 genotypes, since the genes controlling virus transmission are additive in effect (8,9,34), and as we expected, the refractive F2 genotypes expressed some of the proteins in a manner similar to that of the competent genotypes. Thirty-two such spots were identified (Tables 2 and 3), 13 of which were aphid proteins upregulated in the competent genotypes and 7 of which were downregulated in the competent genotypes ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Parthenogenetically reproducing aphid colonies were maintained on caged barley (Hordeum vulgare) at 20°C with an 18-h photo period as described previously (35). The origins and CYDV-RPV transmission efficiencies of the parental genotypes of S. graminum, Sg-SC and Sg-F, as well as the F2 genotypes A3, C2, K2, and K3 were described previously (8,9,32,77). Additional F2 genotypes, MM1, BB1, CC1, and CC6, are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sexual crosses with aphids with these genotypes coupled with transmission efficiency studies on F 1 and F 2 progeny indicated that the hybrids segregated not only for the ability to transmit each virus species but also for which cellular barrier (hindgut or ASG) blocked virus movement and transmission (3). Subsequent genetic analysis indicated that genetic inheritance of vector competence was a multigenic trait involving only a few major genes and several minor genes that function in an additive manner (4). Evidence that multigenetic factors in aphids regulated luteovirus transmission is consistent with other work describing transmission barriers to luteovirus transmission occurring at different sites in aphid tissues, such as the gut and salivary gland (12).…”
mentioning
confidence: 99%